S93 Systematic follow-up of patients following acute pulmonary embolism is associated with an increased incidence of chronic thromboembolic pulmonary hypertension and less severe disease. (11th November 2022) - Durrington, C; Armstrong, I; Charalampopoulos, A; Condliffe, R; Devey, T; Elliot, C; Hameed, A; Hamilton, N; Hill, C; Hurdman, J; Lewis, RA; Maclean, R; et al.
Abstract : Introduction: There are limited data on the incidence of chronic thromboembolic pulmonary hypertension (CTEPH). The Sheffield Pulmonary Vascular Disease Unit (SPVDU) serves a population of 15 million. In Sheffield (population 600, 000) a pulmonary embolism (PE) follow-up clinic was established in 2010. The study aim was to assess the impact of a PE follow-up clinic on the diagnostic rate and severity of CTEPH. Methods: Patients diagnosed with CTEPH (2010–2020) included Sheffield patients referred from the PE clinic (Group A), those not referred through the PE clinic (Group B), and patients with suspected PH referred from outside Sheffield (Group C). CTEPH was defined according to the recommendations of the 6th World Symposium on pulmonary hypertension and required supportive imaging, a mean pulmonary artery pressure (mPAP) ≥20 mmHg at right heart catheterisation, with other causes of PH excluded. Results: Over the 10-year period, 854 patients were diagnosed with CTEPH by the SPVDU. Of 1944 patients evaluated over the same time period in the PE-follow-up clinic, 32 were diagnosed with CTEPH with a cumulative incidence at 2 years of 1.3%. There were 73 Sheffield patients with CTEPH (Groups A and B) giving a diagnostic rate of 12.2/million/year based on a referral population of 600, 000, compared to 5.2/million/year for 781 patients with CTEPH referred from outside of Sheffield. Haemodynamic evaluation (mean pulmonary arterial pressure (mPAP) and pulmonary vascular resistance (PVR)) at initial right heart catheterisation and incremental shuttle walking test (ISWT) were compared across the three groups and displayed in table 1 . Conclusion: The introduction of an acute PE follow-up clinic identifies patients with CTEPH with less severe haemodynamic disease and increased functional ability as demonstrated by an ISWT. Introduction of a clinic to evaluate patients following PE, in combination with current UK approaches to the assessment of suspected pulmonary hypertension, can achieve diagnostic rates for CTEPH of 12.2/million/year.